Resilience of Islamic Banking in Conventional Financial Markets - Paschal J. Bukanu; Rosemary Jotham Mukama (Universiti Sains Islam Malaysia, 2025)
The Journal of Muamalat and Islamic Finance Research, Volume 22 Issue 2 Page (77–94)